Mechanical assessment of two hybrid plate designs for pancarpal canine arthrodesis under cyclic loading - Zderic, Ivan; Varga, Peter; Styger, Ursula; Drenchev, Ludmil; Gueorguiev, Boyko; Asimus, Erik; Saunders, W. Brian; Kowaleski, Michael; Boudrieau, Randy J.; Déjardin, Loic M. (Frontiers in Bioengineering and Biotechnology, 2023)
Pancarpal canine arthrodesis (PCA) sets immobilization of all three carpal joints via dorsal plating to result in bony fusion. Whereas the first version of the plate uses a round hole (RH) for the radiocarpal (RC) screw region, its modification into an oval hole (OH) in a later version improves versatility in surgical application. The aim of this study was to mechanically investigate the fatigue life of the PCA plate types implementing these two features–PCA-RH and PCA-OH. Ten PCA-RH and 20 PCA-OH stainless steel (316LVM) plates were assigned to three study groups (n = 10). All plates were pre-bent at 20° and fixed to a canine forelimb model with simulated radius, RC bone and third metacarpal bone. The OH plates were fixed with an RC screw inserted either most proximal (OH-P) or most distal (OH-D). All specimens were cyclically tested at 8 Hz under 320 N loading until failure. Fatigue life outcome measures were cycles to failure and failure mode. Cycles to failure were higher for RH plate fixation (695,264 ± 344,023) versus both OH-P (447,900 ± 176,208) and OH-D (391,822 ± 165,116) plate configurations, being significantly different between RH and OH-D, p = 0.03. No significant difference was detected between OH-P and OH-D configurations, p = 0.09. Despite potential surgical advantages, the shorter fatigue life of the PCA-OH plate design may mitigate its benefits compared to the plate design with a round radiocarpal screw hole. Moreover, the failure risk of plates with an oval hole is increased regardless from the screw position in this hole. Based on these findings, the PCA plate with the current oval radiocarpal screw hole configuration cannot be recommended for clinical use.